Low hydrogen iron powder covered electrode

JP7651347B2Active Publication Date: 2025-03-26NIPPON STEEL WELDING & ENGINEERING CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021056218
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-29
Publication Date
2025-03-26
Estimated Expiration
2041-03-29

Smart Images

  • Figure 0007651347000001
    Figure 0007651347000001
  • Figure 0007651347000002
    Figure 0007651347000002
  • Figure 0007651347000003
    Figure 0007651347000003
Patent Text Reader

Abstract

To provide a low-hydrogen iron-powder coated arc welding rod for 780 MPa class high-strength steel, the welding rod having good welding workability and being capable of providing a weld metal with appropriate strength and low-temperature toughness.SOLUTION: A low-hydrogen iron-powder coated arc welding rod contains Mn: 2.5-5.0%, Ni: 7.5-13.5%, Mo: 0.3-1.3%, Si: 2.0-5.0%, SiO2 conversion value of Si oxides: 4.0-7.5%, Ti: 0.2-2.0%, TiO2 conversion value of Ti oxides: 2.0-5.0%, metal carbonates: 30-50%, metal fluorides: 6-16%, Al2O3 conversion value: 2.0% or less, MgO conversion value: 0.8% or less, total of Na and K conversion values: 1.5-3.0%, and Fe: 10-25%, by %mass to the total mass of the coating material, and is characterized in that the coating is performed at a coverage rate of 25-40%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an iron powder low-hydrogen covered metal arc welding electrode which has good arc stability, a tensile strength of 780 MPa or more, and excellent low-temperature toughness at -80°C, particularly in arc welding using a DC power source. [Background technology]

[0002] Low-hydrogen covered electrodes have good arc stability and excellent crack resistance and low-temperature toughness of the weld metal, and are therefore widely used in areas with strong restraint and for welding high-tensile steel.

[0003] On the other hand, with the recent increase in the size of welded structures, there is a demand for higher strength steel materials to be used. Also, in order to ensure safety in large marine structures and spherical tanks aimed at the development of natural resources, it is important to further improve the low-temperature toughness of the weld metal and ensure excellent mechanical performance, such as by ensuring sufficient strength. However, since the compatibility of high strength and low-temperature toughness in weld metal is generally a contradictory property, the development of a new method to achieve both high strength and low-temperature toughness is desired.

[0004] In response to this situation, several proposals have been made as a means for improving the mechanical properties of the weld metal. For example, Patent Document 1 discloses a technology relating to a low-hydrogen covered metal arc welding rod containing 3.5 to 12.5 mass % of Ni powder for a covered metal arc welding rod, which has good productivity, excellent welding workability, and can ensure the toughness of the weld metal, based on the total mass of the coating. However, the technology described in Patent Document 1 does not disclose the use of a DC power source, and there is a problem that one-sided melting of the coating and magnetic blow occur during DC welding, making it impossible to obtain sufficient welding workability.

[0005] Also, Patent Document 2 discloses a technology for a low-hydrogen covered electrode that has excellent arc stability and excellent weld metal strength and toughness at low temperatures in multi-layer welding such as circumferential welding of steel pipes using a DC power source. However, the technology described in Patent Document 2 is for multi-layer circumferential welding of steel pipes of 550 MPa class or more, and there is a problem that it is not applicable to welded joints using 780 MPa class high tensile steel due to insufficient strength.

[0006] On the other hand, Patent Document 3 discloses a technology of a low-hydrogen covered metal arc welding electrode which has excellent crack resistance, strength and toughness of the weld metal, good welding workability in all positions, and excellent moisture absorption resistance and adhesion of the coating material when welding high-tensile steel with a proof stress of 690 MPa or more. However, the technology described in Patent Document 3 has a problem that it is not possible to obtain good low-temperature toughness at -80°C when welding high-tensile steel with a tensile strength of 780 MPa or more (proof stress of 690 MPa or more) because of the small amount of Ni. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2012-143809 A [Patent Document 2] JP 2015-196183 A [Patent Document 3] JP 2017-001053 A Summary of the Invention [Problem to be solved by the invention]

[0008] In Japan, low-hydrogen covered electrodes are generally designed to be used for welding with an AC power source. Recently, however, for on-site welding of spherical tanks and marine structures overseas, there has been a demand for the development of low-hydrogen covered electrodes that can be used with DC power sources, which are cheaper power sources.

[0009] When a low-hydrogen covered electrode is used for welding with a DC power source, magnetic blow and one-sided melting of the coating material occur, making the arc unstable and making it difficult to obtain a sound bead. For this reason, there is a demand for the development of an iron powder low-hydrogen covered electrode that has excellent arc stability and good mechanical properties of the weld metal even when a DC power source is used.

[0010] The present invention has been devised in view of the above problems, and has an object to provide an iron powder, low hydrogen type covered metal arc welding electrode for 780 MPa class high tensile steel, which has good welding workability such as arc stability and good low temperature toughness at -80°C in multi-pass welding using a DC power source for higher strength 780 MPa class high tensile steel. [Means for solving the problem]

[0011] The present invention relates to a low-hydrogen iron powder covered metal arc welding electrode in which a steel core wire is coated with a coating material, the coating rate of the coating material being 25-40% by mass relative to the total mass of the welding rod, and the composition of the coating material being 2.5-5.0% Mn, 7.5-13.5% Ni, 0.3-1.3% Mo, 2.0-5.0% Si, 4.0-7.5% total Si oxides in terms of SiO2, 0.2-2.0% Ti, and 0.2-2.0% Ti, the total Ti oxides in terms of TiO2 being 0.2-0.5% by mass relative to the total mass of the coating material. The coating material is characterized in that it contains a total of 2.0 to 5.0% of one or more metal carbonates: 30 to 50% of one or more metal fluorides: 6 to 16% of one or more metal fluorides, a total of Al oxides in terms of Al2O3: 2.0% or less, a total of Mg oxides in terms of MgO: 0.8% or less, a total of one or more of sodium oxide, sodium fluoride, potassium oxide and potassium fluoride: a total of 1.5 to 3.0% in terms of Na and K, and Fe: 10 to 25%, and the total of the remainder consisting of impurities is 1.0% or less.

[0012] It also contains Ca oxide, The coating material has a total Ca oxide content, calculated as CaO, of 0.5% or less by mass % relative to the total mass of the coating material.

[0013] It also contains Zr oxide, The coating material has a total mass of Zr oxide calculated as ZrO2 of 1.5% or less based on the total mass of the coating material. Effect of the Invention

[0014] The low hydrogen iron powder covered metal arc welding electrode of the present invention can provide strength equal to or greater than that of steel in multi-layer welding of 780 MPa class high tensile steel using a DC power source, and has good welding workability such as arc stability, and stable toughness at low temperatures. Therefore, the reliability of welded joints for various steel structures can be significantly improved. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] In order to solve the above-mentioned problems, the present inventors conducted a detailed study on an iron powder low-hydrogen covered metal arc welding electrode, in particular the composition of the coating material thereof, which is capable of obtaining strength equal to or greater than the above strength, good welding workability such as arc stability, and stable low-temperature toughness in multi-pass welding of 780 MPa class high tensile steel using a DC power source.

[0016] As a result, the following findings were obtained, and the present invention was developed by adjusting the various components according to these findings.

[0017] (1) The strength of the weld metal can be ensured by adjusting the content of Mn, Ni, and Mo to an appropriate amount.

[0018] (2) The toughness of the weld metal at low temperatures can be improved by optimizing the content of metal carbonate, Si, and Ti and the coating rate on the steel core wire.

[0019] (3) In order to stabilize the arc and reduce the amount of spatter generated, which are related to the welding workability, the total amount of one or more of Si, Ti, Ti oxide (converted into TiO2), metal carbonate, metal fluoride, and sodium oxide, sodium fluoride, potassium oxide, and potassium fluoride can be adjusted to an appropriate amount.

[0020] (4) The bead shape and bead appearance can be improved by adjusting the total content of metal carbonates, metal fluorides, Ti oxide (converted into TiO2), Si oxide (converted into SiO2), and Mg oxide (converted into MgO) to appropriate amounts.

[0021] (5) The slag removability can be improved by adjusting the total amount of metal carbonate, silicon oxide in terms of SiO2, metal carbonate, metal fluoride, and aluminum oxide in terms of Al2O3 to an appropriate amount.

[0022] (6) In order to prevent rod burn, in which the welding rod itself becomes red hot, the Fe content can be adjusted to an appropriate amount. In order to prevent one-sided melting of the welding rod protective tube, the metal fluoride and Fe contents can be adjusted to an appropriate amount. The productivity of the welding rod, such as the paintability of the coating agent, can be improved by adjusting the total amount of one or more of sodium oxide, sodium fluoride, potassium oxide and potassium fluoride to an appropriate amount.

[0023] (7) By adjusting the total amount of Ca oxides converted into CaO, it is possible to improve arc stabilization and welding defects such as poor fusion, and by adjusting the total amount of Zr oxides converted into ZrO2, it is possible to improve the bead shape and bead appearance.

[0024] The reasons for limiting the range of each composition in the coating of the low hydrogen iron powder covered metal arc welding electrode of the present invention will be described in detail below. The content of each component in the coating of the low hydrogen iron powder covered metal arc welding electrode is expressed in mass% relative to the total mass of the coating, and when expressing the mass%, it is simply written as %.

[0025] [Covering rate: 25-40% by mass of the total mass of the welding rod] The coverage rate of the coating material on the outer circumference of the steel core wire has a large effect on the shielding resistance during welding. If the coverage rate is less than 25% by mass of the coating material relative to the total mass of the iron powder low hydrogen type covered metal arc welding electrode (hereinafter simply referred to as %), the coating material itself becomes less, resulting in insufficient shielding, and the N content in the weld metal increases, reducing the toughness of the weld metal. On the other hand, if the coverage rate of the coating material exceeds 40%, the amount of slag increases too much and the arc becomes unstable. Therefore, the coverage rate is set to 25 to 40%.

[0026] [Mn: 2.5-5.0%] Mn is added from metal Mn, Fe-Mn, Fe-Si-Mn, etc., and is an element necessary as a deoxidizer for weld metal, and has the effect of refining the weld metal structure and increasing the low-temperature toughness and strength of the weld metal. If Mn is less than 2.5%, the strength and low-temperature toughness of the weld metal decrease. Also, if Mn is less than 2.5%, deoxidation is insufficient and blowholes are likely to occur in the weld metal. On the other hand, if Mn exceeds 5.0%, the strength of the weld metal becomes excessively high and the toughness decreases. Therefore, Mn is set to 2.5 to 5.0%.

[0027] [Ni:7.5~13.5%] Ni is added as metallic Ni and has the effect of improving the strength and low-temperature toughness of the weld metal. If Ni is less than 7.5%, the strength and low-temperature toughness of the weld metal decrease. On the other hand, if Ni exceeds 13.5%, the strength of the weld metal becomes excessively high. Therefore, Ni is set to 7.5 to 13.5%.

[0028] [Mo: 0.3-1.3%] Mo is added in the form of metal Mo, Fe-Mo, etc., and has the effect of further improving the strength of the weld metal. If Mo is less than 0.3%, the strength of the weld metal decreases. On the other hand, if Mo exceeds 1.3%, the strength of the weld metal becomes excessively high and the toughness decreases. Therefore, Mo is set to 0.3 to 1.3%.

[0029] [Si: 2.0~5.0%] Silicon is added from metal silicon, Fe-Si, Fe-Si-Mn, etc., and is used for the purpose of deoxidizing the weld metal. If the silicon content is less than 2.0%, deoxidation is insufficient, making blowholes more likely to occur in the weld metal and making the arc unstable. On the other hand, if the silicon content exceeds 5.0%, low-melting-point oxides are precipitated at the grain boundaries of the weld metal, reducing the low-temperature toughness of the weld metal. Therefore, the silicon content is set to 2.0-5.0%.

[0030] [Total of silicon oxides converted into SiO2: 4.0-7.5%] Silicon oxide is added from silica sand, zircon sand, potassium feldspar, solid components of water glass such as sodium silicate and potassium silicate, wollastonite, etc., and has the effect of increasing the viscosity of the molten slag, ensuring slag with appropriate viscosity, and improving the bead shape. If the silicon oxide content is less than 4.0%, the viscosity of the molten slag will be low and the bead shape will be poor. On the other hand, if the SiO2 equivalent value of silicon oxide exceeds 7.5%, the slag will become glassy and the slag removability will be poor. Therefore, the SiO2 equivalent value of silicon oxide is set to 4.0 to 7.5%.

[0031] [Ti: 0.2-2.0%] Ti is added from metallic Ti, Fe-Ti, etc., and is effective as a deoxidizer, and at the same time, it has the effect of lowering the potential gradient of the arc and stabilizing the arc. In addition, it has the effect of refining the weld metal structure and improving the low-temperature toughness of the weld metal. If Ti is less than 0.2%, this effect is not obtained and the arc becomes unstable. Also, if Ti is less than 0.2%, the amount of oxygen in the weld metal increases and the microstructure of the weld metal is not refined, so the low-temperature toughness of the weld metal decreases. On the other hand, if Ti exceeds 2.0%, the precipitation of Ti oxide in the weld metal increases, and the low-temperature toughness of the weld metal decreases.

[0032] [Total Ti oxides converted into TiO2: 2.0-5.0%] Ti oxide is added from rutile, titanium oxide, titanium slag, calcium titanate, etc., and has the effect of stabilizing the arc and adjusting the viscosity of the molten slag to improve the bead shape. If the Ti oxide content in terms of TiO2 is less than 2.0%, the arc becomes unstable and the bead shape becomes poor. On the other hand, if the Ti oxide content in terms of TiO2 exceeds 5.0%, the viscosity of the molten slag increases and the fluidity of the slag deteriorates, resulting in a convex bead shape. Therefore, the Ti oxide content is set to 2.0 to 5.0%.

[0033] [Metal carbonates (single or multiple): 30~50%] Metal carbonates are added from calcium carbonate, magnesium carbonate, barium carbonate, etc., and decompose with the heat of the arc to generate CO2 gas, which has the effect of protecting the weld metal from the atmosphere. If the total of one or more metal carbonates is less than 30%, the shielding effect is insufficient and blowholes are likely to occur. If the total of one or more metal carbonates is less than 30%, nitrogen from the atmosphere is mixed into the weld metal, reducing low-temperature toughness. On the other hand, if the total of one or more metal carbonates exceeds 50%, the arc becomes unstable, the bead shape becomes convex, and slag removability is also poor. Therefore, the total of one or more metal carbonates is set to 30-50%.

[0034] [Metal fluorides (single or multiple): 6-16%] Metal fluorides are added from fluorite, magnesium fluoride, aluminum fluoride, lithium fluoride, sodium fluoride, potassium silicofluoride, etc., and have the effect of adjusting the fluidity of the molten slag and improving the bead appearance. If the total of one or more metal fluorides is less than 6%, the fluidity of the molten slag is poor, the slag encapsulation is poor, and the bead appearance is poor. On the other hand, if the total of one or more metal fluorides exceeds 16%, the shape of the covering tube becomes incomplete, resulting in a one-sided melting state and an unstable arc. Therefore, the total of one or more metal fluorides is set to 6-16%.

[0035] [Total of Al oxides converted to Al2O3: 2.0% or less] Aluminum oxides are added from alumina, potassium feldspar, etc., and have the effect of stabilizing the arc and improving the bead shape. However, if the total amount of aluminum oxides (Al2O3) exceeds 2.0%, the slag becomes glassy and the slag removability becomes poor. Therefore, the total amount of aluminum oxides (Al2O3) should be 2.0% or less.

[0036] [Total of Mg oxides converted to MgO: 0.8% or less] Mg oxide is added from magnesium oxide, magnesia clinker, etc., and has excellent heat resistance and is effective in suppressing the one-sided melting of the coating material. However, if the total of Mg oxide converted into MgO exceeds 0.8%, the viscosity of the molten slag increases, and the bead shape becomes convex. Therefore, the total of Mg oxide converted into MgO should be 0.8% or less.

[0037] [Total of one or more of sodium oxide, sodium fluoride, potassium oxide and potassium fluoride: 1.5% to 3.0% in terms of sodium and potassium] Na is added from Na oxides such as sodium silicate and other solid components of water glass, and Na fluorides such as sodium fluoride, and K is added from potassium silicate and other solid components of water glass, K oxides such as potassium feldspar, and K fluorides such as potassium silicate fluoride, and these have the effect of improving the paintability during the manufacture of welding rods and the stability of the arc during welding. If the total of one or more of Na oxides, Na fluorides, K oxides, and K fluorides is less than 1.5% in terms of Na and K, the arc becomes unstable. In addition, the paintability during production deteriorates, and cracks are more likely to occur on the coating surface during the manufacture of welding rods, reducing the productivity of the covered arc welding rod. On the other hand, if the total of Na and K exceeds 3.0%, the arc blow becomes stronger and the amount of spatter increases. Therefore, the total of one or more of sodium oxide, sodium fluoride, potassium oxide and potassium fluoride is 1.5 to 3.0% in terms of sodium and potassium. The sodium and potassium values ​​include 0%.

[0038] [Fe: 10-25%] Fe is added from iron powder, iron alloy powder such as Fe-Mn and Fe-Mo, or iron oxide, and has the effect of reducing the potential gradient of the arc, shortening the arc length, and preventing one-sided melting of the coating material, and is the most important raw material, especially in welding using a DC power source. If Fe is less than 10%, the arc length becomes long and one-sided melting of the coating material is likely to occur. On the other hand, if Fe exceeds 25%, the thermal conductivity becomes high, and in welding with a covered metal arc welding rod, the covered metal arc welding rod itself becomes red hot (hereinafter referred to as rod burn) in the latter half of welding, making welding difficult. Therefore, Fe is set to 10-25%.

[0039] [Total of Ca oxides converted into CaO: 0.5% or less] Ca oxide is added from calcium titanate, wollastonite, etc., and is effective in stabilizing the arc and reducing spatter generation. If the total of Ca oxide converted into CaO exceeds 0.5%, the arc becomes weak and unstable, and welding defects such as poor fusion are likely to occur. Therefore, the total of Ca oxide converted into CaO is set to 0.5%.

[0040] [Total of Zr oxides converted into ZrO2: 1.5% or less] Zirconium oxide is added from zircon sand, zirconia, etc., and has a high melting point of 2700℃, so it has stable fire resistance even when the coating material and steel core wire are overheated, and is effective in preventing the coating material from melting one-sidedly. If the total of Zr oxide converted into ZrO2 exceeds 1.5%, the viscosity of the molten slag increases, the fluidity of the slag decreases, and the bead shape becomes convex. Therefore, the total of Zr oxide converted into ZrO2 should be 1.5% or less.

[0041] The balance of the coating material of the iron powder low hydrogen type covered metal arc welding electrode of the present invention is impurities contained in the coating material and the alloy powder. Hectorite, mica, etc. are used as the coating material. Impurities contained in the alloy powder include P, S, Cu, Nb, V, and B. In particular, P and S both generate compounds with low melting points and reduce the toughness of the weld metal, so the total amount of impurities is adjusted to 1.0% or less.

[0042] The steel core wire used is preferably JIS G3523:1980 SWY11, but does not have to be SWY11. The C content of the steel core wire is preferably 0.08% or less, and the C content can be adjusted appropriately from the coating material to adjust the strength. The P content of the steel core wire decreases toughness, so it is preferable that it is 0.010% or less, and S decreases the fluidity of the slag, so it is preferable that it is 0.010% or less. EXAMPLES

[0043] The effects of the present invention will now be described in more detail with reference to examples.

[0044] A JIS G3523:1980 SWY11 steel core wire (C: 0.08%, Si: 0.02%, Mn: 0.46%, P: 0.009%, S: 0.006%) with a diameter of 4.0 mm and a length of 400 mm was coated with a coating agent having the composition shown in Table 1 at the coverage shown in Tables 1 and 2, and then dried to produce various iron powder low hydrogen type covered metal arc welding electrodes.

[0045] In this case, the composition of the coating material is JIS K0116The ICP emission spectrometry method described in :2014 was used for the investigation. The coating of the prototype welding rod was peeled off, the sample was collected, and the powder sample was pulverized. The powder sample was decomposed using the acid decomposition method or the alkali fusion method. A part of the solution was sprayed and introduced into the argon plasma of the ICP emission spectrometry analyzer, and the emission intensity of the analytical line of the quantitative component or the ratio of the emission intensity of the analytical line of the quantitative component to the emission intensity of the internal standard element was measured. The concentration of the measurement target element in the sample solution was determined from the obtained emission intensity using the calibration curve method. In addition, X-ray diffraction analysis was used for the quantitative analysis of metals and oxides such as Si and SiO2. For example, the amount of Si in the coating was specified using the ICP emission spectrometry method, and the metal Si and oxide Si were measured using the same coating by the X-ray diffraction analysis method, and the quantitative analysis values ​​of each were obtained. In order to improve the analytical accuracy, it is desirable to pulverize the coating into fine particles of 10 μm or less using an agate mortar or the like. The procedure for filling the sample was as follows: a glass sample plate was placed on a flat glass plate measuring 10 cm square and approximately 5 mm thick, and the glass plate was used to hold the plate in a groove approximately 0.5 mm deep. The surface of the sample plate and the sample surface were finished to be flush with each other, and the sample was then analyzed using an X-ray diffraction analyzer.

[0046] [Table 1]

[0047] [Table 2]

[0048] Using the above various prototype welding rods, weld metal test specimens were prepared by forming a backing groove with a groove angle of 20° and a root gap of 16 mm on a 20 mm thick steel plate with the composition shown in Table 3, and using a DC power source under the following conditions: welding current: 170 A, welding heat input: 19 kJ / cm, preheat / interpass temperature: 95-110°C.

[0049] [Table 3]

[0050] [Table 4]

[0051] The welding workability was evaluated by visually inspecting the arc stability, amount of spatter, bead shape and appearance, slag detachability, and the presence or absence of one-sided melting and rod burn during the above welding using each prototype welding rod. After welding, an X-ray transmission test was performed according to AWS A5.5 to check for the presence or absence of welding defects. Tensile test pieces (AWS B4.0:2007) and V-notch impact test pieces (AWS B4.0:2007) were taken from the center of the plate thickness of the weld metal test pieces. In the tensile test, a tensile strength of 820 to 950 MPa was considered good, and for the evaluation of toughness, a Charpy impact test was performed at a test temperature of -80°C, and the average of the absorbed energy of 80 J or more out of five times, excluding the lowest and highest values, was considered good. The test results are summarized in Table 5.

[0052] [Welding workability] (Arc Stability) If the arc was stable during welding and did not disappear, it was rated as good, and if the arc disappeared even once, it was rated as poor.

[0053] (Amount of spatter generated) It is preferable that the amount of spatter generated during welding is small. Specifically, a copper collection box was used to measure the weight of spatter generated during 1 minute of welding to determine the value per unit time (g / min). The spatter was measured five times under the welding conditions shown in Table 4, and the average value was calculated. A value of 2.0 g / min or less was considered good.

[0054] (Bead shape / bead appearance) It is preferable that the bead waveform of the deposited metal is uniform and free of disturbance, and that there is no undercut or overlap that requires rework. It is preferable that the deposited metal has a bead shape with excellent uniformity in the excess height and bead width. Specifically, a case where the bead waveform of the deposited metal is disturbed or where undercut or overlap that requires rework occurs on the bead surface of the deposited metal is determined as defective.

[0055] (Slag removability) It is preferable that the solidified slag on the weld bead surface can be easily removed after welding. After welding, the solidified slag on the weld bead surface was struck with a chipping hammer (total length 300 mm, weight 350 g) by swinging it down lightly in an arc around the handle. If the slag cracked and could then be easily removed, it was rated as good, and if the slag did not crack, it was rated as poor.

[0056] (Partial dissolution of coating material) It is preferable that the arc is generated parallel to the welding rod without any chipping of the coating material during welding, and that the arc spread is uniform and stable. If part of the coating material is chipped during welding, the arc is deflected in a direction other than parallel to the welding rod, and the arc spread is non-uniform, it is rated as defective.

[0057] (stick burn) It is preferable that the coating does not fall off during welding because the welding rod becomes red hot. A welding rod that does not change color during welding is rated as good, and a welding rod that becomes red hot and turns red is rated as bad.

[0058] [Welding defects] Specifically, X-ray examination was performed in accordance with AWS A5.5 to judge the presence or absence of defects in the weld metal. A specimen without any defects was rated as good, and a specimen with even one defect was rated as poor.

[0059] [Table 5]

[0060] Welding rods No. 1 to No. 15 in Tables 1, 2, and 5 are examples of the present invention, and welding rods No. 16 to No. 30 are comparative examples. In the welding rods No. 1 to No. 15, which are examples of the present invention, the amounts of Mn, Ni, Mo, Si, Si oxide in terms of SiO2, Ti, Ti oxide in terms of TiO2, metal carbonate, metal fluoride, total of Al oxide in terms of Al2O3, total of Mg oxide in terms of MgO, total of Na oxide, Na fluoride, total of Na and K values ​​of one or more of K oxide and K fluoride, Fe, and coverage are all appropriate, so the arc condition is good, the amount of spatter generation is small, the condition of the protective tube is good, rod burn does not occur, the bead appearance, bead shape, slag removability, and slag encapsulation are good, and other welding workability is good, productivity is good, there are no welding defects, and the tensile strength and absorbed energy of the weld metal are good, resulting in extremely satisfactory results.

[0061] Furthermore, since No. 4, No. 8, and No. 10 had an appropriate total amount of Ca oxide converted into CaO, the arc condition was better than the other inventive examples, and there was less spatter.

[0062] In addition, since the total amount of Zr oxide converted into ZrO2 was appropriate in Nos. 2, 6, and 14, the one-sided dissolution of the coating material was suppressed more than in the other inventive examples.

[0063] Among the comparative examples, welding rod No. 16 had a low coverage rate, so the absorbed energy of the deposited metal was low, and the SiO2 equivalent value of the silicon oxide was high, so the slag removability was poor.

[0064] Welding rod No. 17 had a high Mn content, so the tensile strength of the weld metal was high and the absorbed energy was low. Also, because it had a low Si content, the arc became unstable and blowholes occurred.

[0065] Welding rod No. 18 had a low Mn content and a low SiO2 equivalent value of Si oxide, so the tensile strength of the weld metal was low, the absorbed energy was low, blowholes occurred, and the bead shape was poor. Also, the total Al2O3 content of Al oxide was high, so the slag removability was poor.

[0066] Welding rod No.19 had a high coverage rate, which resulted in an unstable arc. In addition, the total amount of one or more metal fluorides was low, which resulted in poor slag coverage and poor bead appearance. In addition, the amount of Ni was high, which resulted in high tensile strength of the deposited metal.

[0067] Welding rod No. 20 had low Ni content, so the tensile strength and absorbed energy of the deposited metal were low. Also, because it had a lot of Fe and the TiO2 equivalent value of Ti oxide was low, rod burning occurred, the arc became unstable, and the bead shape was poor.

[0068] Welding rod No. 21 had high tensile strength of the weld metal and low absorbed energy because it contained a lot of Mo. Also, because it contained a lot of metal fluoride, one-sided melting occurred and the arc became unstable.

[0069] Welding rod No. 22 had a low Mo content and a high TiO2 equivalent value, which resulted in low tensile strength of the weld metal, poor slag fluidity, poor encapsulation, and a convex bead shape. In addition, Ca oxide was added, but the total CaO equivalent value of Ca oxide was high, which resulted in an unstable arc and poor fusion.

[0070] Welding rod No. 23 had a large amount of Si and a large total MgO equivalent value of MgO oxide, so the absorbed energy was low and the bead shape was convex.

[0071] Welding rod No. 24 had a high Ti content and a low total of Na-equivalent and K-equivalent values, so the absorbed energy was low, the arc was unstable, and productivity was poor.

[0072] Welding rod No. 25 had low Ti content, so absorbed energy was low and the arc was unstable. Also, because it had low Fe content, one-sided melting occurred.

[0073] Welding rod No. 26 contained a large amount of metal carbonate, which resulted in poor slag removability, a convex bead shape, and an unstable arc.

[0074] Welding rod No. 27 had a low metal carbonate content, so the absorbed energy was low and blowholes occurred.

[0075] Welding rod No. 28 had a strong arc and a lot of spatter because the total of the Na equivalent value and the K equivalent value was high. Furthermore, Zr oxide was added, but the total of the ZrO2 equivalent value of Zr oxide was high, so the bead shape was convex.

Claims

1. In low-hydrogen iron powder covered metal arc welding electrodes in which a coating is applied to the steel core wire, The coverage of the coating material is 25 to 40% by mass relative to the total mass of the welding rod; The composition of the coating agent is expressed as a mass % based on the total mass of the coating agent, Mn: 2.5-5.0%, Ni: 7.5-13.5%, Mo: 0.3 to 1.3%, Si: 2.0 to 5.0%, Silicon oxide SiO 2 Total conversion value: 4.0-7.5%, Ti: 0.2-2.0%, Ti oxide TiO 2 Total conversion value: 2.0-5.0%, Total of one or more metal carbonates: 30-50%; One or more metal fluorides in total: 6 to 16%; Al oxide Al 2 O 3 Total conversion value: 2.0% or less, The total amount of magnesium oxides converted into MgO is 0.8% or less. Sum of one or more of Na oxide, Na fluoride, K oxide and K fluoride: 1.5 to 3.0% in terms of Na and K, Fe: 10 to 25%; 1. An iron powder low hydrogen type covered metal arc welding electrode, characterized in that it is coated with a coating material having a total impurity balance of 1.0% or less.

2. Further containing Ca oxide, The coating agent is, in mass % based on the total mass of the coating agent, Total Ca oxide converted to CaO: 0.5% or less 2. The low hydrogen iron powder covered metal arc welding electrode according to claim 1,

3. Further containing Zr oxide, The coating agent is, in mass % based on the total mass of the coating agent, Zr oxide ZrO 2 Total conversion value: 1.5% or less 3. The low hydrogen iron powder covered metal arc welding electrode according to claim 1,

Citation Information

Patent Citations

  • Welding rod for sea atmosphere corrosion resisting steel

    CN107598414A

  • Low hydrogen covered electrode

    JP1996257791A

  • Low hydrogen coated arc welding electrode

    JP1997327793A

  • Ni POWDER FOR COVERED ARC WELDING ELECTRODE, AND LOW-HYDROGEN TYPE COVERED ARC WELDING ELECTRODE

    JP2012143809A

  • Low hydrogen type coated electrode

    JP2015196183A